Analysis Of The Influence Of Product Quality And Price On Purchasing Decisions With Satisfaction As A Mediation Variable Using PLS-SEM (Case Study On Sugarku Drink In Dradahblumbang Village) - Chindar Utari; Sabilar Rosyad (Jurnal Scientia, 2024)
This research aims to determine the effect of product quality and price on purchasing decisions with satisfaction as a mediating variable using PLS-SEM (case study of Sugarku Drinks in Dradahblumbang Village). The type of research used is quantitative research. The population in this study were consumers who had purchased sugarku drinks. The sample in this study amounted to 120 respondents. The sampling technique uses the purposive sampling method. Data collection in this research used location survey methods and distributing questionnaires. The data analysis technique used is PLS (Partial Least Square) using a supporting instrument, namely SmartPLS 3 software. The results of direct influence research show that product quality has a positive and significant effect on purchasing decisions. Product quality has a positive and significant effect on satisfaction. Price has a positive and significant effect on purchasing decisions. Price has a positive and significant effect on satisfaction. Satisfaction has a positive and significant effect on purchasing decisions. while the results of the indirect influence show that satisfaction is able to mediate product quality on purchasing decisions positively and significantly. Satisfaction is able to mediate price on purchasing decisions positively and significantly.